Continuity of primary care for type 2 diabetes and hypertension and its association with health outcomes and disease control: insights from Central Vietnam - Quynh-Anh Le Ho Thi; Peter Pype; Johan Wens; Huy Nguyen Vu Quoc; Anselme Derese; Wim Peersman; Nhon Bui; Huyen Nguyen Thi Thanh; Tam Nguyen Minh (BMC, 2024)
Abstract Background Vietnam is undergoing a rapid epidemiological transition with a considerable burden of non-communicable diseases (NCDs), especially hypertension and diabetes (T2DM). Continuity of care (COC) is widely acknowledged as a benchmark for an efficient health system. This study aimed to determine the COC level for hypertension and T2DM within and across care levels and to investigate its associations with health outcomes and disease control. Methods A cross-sectional study was conducted on 602 people with T2DM and/or hypertension managed in primary care settings. We utilized both the Nijmegen continuity of care questionnaire (NCQ) and the Bice - Boxerman continuity of care index (COCI) to comprehensively measure three domains of COC: interpersonal, informational, and management continuity. ANOVA, paired-sample t-test, and bivariate and multivariable logistic regression analysis were performed to examine the predictors of COC. Results Mean values of COC indices were: NCQ: 3.59 and COCI: 0.77. The proportion of people with low NCQ levels was 68.8%, and that with low COCI levels was 47.3%. Primary care offered higher informational continuity than specialists (p < 0.01); management continuity was higher within the primary care team than between primary and specialist care (p < 0.001). Gender, living areas, hospital admission and emergency department encounters, frequency of health visits, disease duration, blood pressure and blood glucose levels, and disease control were demonstrated to be statistically associated with higher levels of COC. Conclusions Continuity of primary care is not sufficiently achieved for hypertension and diabetes mellitus in Vietnam. Strengthening robust primary care services, improving the collaboration between healthcare providers through multidisciplinary team-based care and integrated care approach, and promoting patient education programs and shared decision-making interventions are priorities to improve COC for chronic care.